Stakes of Knowing the Truth: A Motivational Perspective on the Popularity of a Controversial Scientific Theory - Morisseau, Tiffany; Branch, T. Y.; Origgi, Gloria (Frontiers in Psychology, 2021)
The aim of this article is to provide a different perspective on people’s beliefs regarding controversial scientific information. We emphasize that, although people generally aim at getting a fair representation of reality, accuracy about scientific issues only matters to the extent that individuals perceive it as useful to achieve their own goals. This has important consequences in terms of how anti-science attitudes as well as epistemically questionable beliefs must be interpreted, which has consequences for addressing misinformation. We argue that most people who endorse scientific misinformation are not truly interested in its accuracy, and rather that plausibility at face value often suffices when it is meant to be used for social purposes only. We illustrate this view with the example of hydroxychloroquine, which was considered as potential treatment for Covid-19, and which has been the subject of much media hype and public concern, particularly in France.